2013
DOI: 10.4137/sart.s12756
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Nicotine Levels Selection and Patterns of Electronic Cigarette use in a Group of “Vapers” Who Had Achieved Complete Substitution of Smoking

Abstract: BackgroundElectronic cigarettes (ECs) are alternative-to-smoking nicotine delivery devices; consumers (commonly called vapers) use them in order to reduce or completely substitute smoking. The European Commission has released a proposal for a new Tobacco Product Directive that might reduce availability of nicotine-containing products, including ECs. In this study, the EC use patterns in subjects who have completely substituted smoking with EC use were examined by personal interviews. The study focused on nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 33 publications
9
88
0
2
Order By: Relevance
“…Although replication in a more highly dependent sample of abstinent smokers with a longer follow up time after e-cigarette use is essential, we can tentatively conclude that: i) cigarette-like appearance is important for many smokers when choosing an e-cigarette device although individual factors predicting choice remain unclear; ii) first generation cigalike devices have the ability to be as effective as second generation devices for reducing cigarette urges and WS; iii) second generation devices may be more satisfying to use which may explain why more people report successfully quitting with them [25]. Although there is concern that first generation cigalike products in particular may re-normalise smoking, they clearly appeal to many smokers and compare favourably to second generation devices for craving/WS alleviation at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although replication in a more highly dependent sample of abstinent smokers with a longer follow up time after e-cigarette use is essential, we can tentatively conclude that: i) cigarette-like appearance is important for many smokers when choosing an e-cigarette device although individual factors predicting choice remain unclear; ii) first generation cigalike devices have the ability to be as effective as second generation devices for reducing cigarette urges and WS; iii) second generation devices may be more satisfying to use which may explain why more people report successfully quitting with them [25]. Although there is concern that first generation cigalike products in particular may re-normalise smoking, they clearly appeal to many smokers and compare favourably to second generation devices for craving/WS alleviation at least in the short term.…”
Section: Discussionmentioning
confidence: 99%
“…Given the evidence that many regular users move on from first to second or third generation devices [23,25,36] we also predicted that those who had some experience of using an e-cigarette in the past would be more likely to opt for a second generation device. That prior e-cigarette use was not a significant predictor here may reflect the fact that most users (82%) had previously used an e-cigarette on fewer than five occasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farsalinos et al 20 also found that e-cig users reported lower dependence on e-cigs than prior cigarette smoking, in a sample of 111 e-cig users with carboxyhemoglobin-validated abstinence from smoking. Overall, the most parsimonious explanation for these results is that e-cig users are generally less nicotine dependent than they were as cigarette smokers.…”
Section: (234)mentioning
confidence: 97%
“…Surveys of dedicated EC users (which were all former smokers) have shown that high nicotine levels are important especially for the initiation of EC use. 3,4 Although nicotine delivery to the aerosol can be similar or higher than tobacco cigarettes, 5,6 clinical studies of EC use have shown that the nicotine absorption potential is significantly lower compared with tobacco cigarettes, even when new generation devices are used. 7 This is mostly attributed to the low speed of nicotine absorption, and clearly indicates that nicotine intoxication is highly unlikely when ECs are used as intended.…”
Section: Nicotine Delivery From Ecsmentioning
confidence: 99%